Electrode for lithium ion secondary battery and method for producing electrode for lithium ion secondary battery

JP7651308B2Active Publication Date: 2025-03-26HONDA MOTOR CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021011628
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-28
Publication Date
2025-03-26
Estimated Expiration
2041-01-28

Smart Images

  • Figure 0007651308000001
    Figure 0007651308000001
Patent Text Reader

Abstract

To provide an electrode for a lithium ion secondary battery capable of increasing the binding force of an electrode active material without increasing the amount of a binder and obtaining a favorable energy density of a lithium ion secondary battery, and a manufacturing method of the same.SOLUTION: An electrode for a lithium ion secondary battery includes an electrode active material, a dendritic polymer, and a binder, and the dendritic polymer is chemically bonded to the surface of the electrode active material, and the dendritic polymer and the binder are chemically bonded.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode for a lithium ion secondary battery and a method for producing the electrode for a lithium ion secondary battery. [Background technology]

[0002] Conventionally, lithium ion secondary batteries have been widely used. Electrodes for lithium ion secondary batteries are formed by binding powder of an electrode active material to a current collector using a binder. It is known that the electrodes of lithium ion secondary batteries expand and contract with charging and discharging, causing capacity degradation of the lithium ion secondary battery. For this reason, a technology is known for suppressing capacity degradation of lithium ion secondary batteries with charging and discharging by adjusting the type and content of the binder (for example, see Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2000-285966 A Summary of the Invention [Problem to be solved by the invention]

[0004] As described in the cited reference 1, there is a problem that the binding strength of the binder decreases with charging and discharging when the electrode active material is only bound by the binder. If the amount of binder is increased, the binding strength can be strengthened and the expansion and contraction of the electrode can be suppressed. However, there are problems that the wettability of the electrolyte decreases, resulting in a decrease in electrode performance, and that the impregnation of the electrolyte decreases, resulting in a longer aging time during electrode production. In addition, there is also a problem that the electrode swells when impregnated with the electrolyte, resulting in a decrease in the density of the electrode active material, resulting in a decrease in the energy density of the lithium-ion secondary battery.

[0005] The present invention has been made in view of the above, and has an object to provide an electrode for a lithium ion secondary battery, which can increase the binding strength of an electrode active material without increasing the amount of binder, and can provide a preferable energy density of the lithium ion secondary battery, and a method for manufacturing the same. [Means for solving the problem]

[0006] (1) The present invention provides an electrode for a lithium ion secondary battery, comprising an electrode active material, a dendritic polymer, and a binder, the dendritic polymer being chemically bonded to a surface of the electrode active material; The present invention relates to an electrode for a lithium ion secondary battery, in which the dendritic polymer and the binder are chemically bonded to each other.

[0007] According to the invention of (1), it is possible to provide an electrode for a lithium ion secondary battery that can increase the binding strength of the electrode active material without increasing the amount of binder and can obtain a preferable energy density of the lithium ion secondary battery.

[0008] (2) The electrode for a lithium ion secondary battery according to (1), wherein the electrode active material is a negative electrode active material, and a density of a negative electrode mixture layer including the electrode active material, the dendritic polymer, and the binder after impregnation with an electrolyte solution is 95% or more of a density of the negative electrode mixture layer before impregnation with the electrolyte solution.

[0009] According to the invention of (2), it is possible to prevent a decrease in density of the electrode active material of the electrode due to impregnation with the electrolyte. In addition, it is possible to minimize the space inside the battery cell that is required in the design of a lithium ion secondary battery to take into account the variation in the thickness and width of the electrode. Therefore, it is possible to improve the volumetric energy density of the lithium ion secondary battery.

[0010] (3) The electrode for a lithium ion secondary battery according to (1) or (2), wherein the electrode active material is a negative electrode active material, and an amount of the dendritic polymer chemically bonded to a surface of the negative electrode active material is 0.1 to 1.0 parts by mass per 100 parts by mass of the negative electrode active material.

[0011] According to the invention (3), the electrode for a lithium ion secondary battery as described in (2) can be obtained.

[0012] (4) The present invention also relates to a method for producing an electrode for a lithium ion secondary battery, the method comprising: an electrode mixture layer forming step of forming an electrode mixture layer on a current collector, the electrode mixture layer including an electrode active material, a dendritic polymer, and a binder; a pressing step of pressing the current collector on which the electrode mixture layer has been formed at a first temperature to form an electrode; and a vacuum drying step of vacuum drying the electrode formed by the pressing step at a second temperature.

[0013] According to the invention of (4), it is possible to manufacture an electrode for a lithium ion secondary battery that can increase the binding strength of the electrode active material without increasing the amount of binder and can obtain a preferable energy density of the lithium ion secondary battery.

[0014] (5) The method for producing an electrode for a lithium ion secondary battery according to (4), wherein the density of the electrode mixture layer after being impregnated with the electrolyte is adjusted to 95% or more of the density of the electrode mixture layer before being impregnated with the electrolyte by adjusting the first temperature and the second temperature.

[0015] According to the invention (5), the electrode for a lithium ion secondary battery according to the invention (2) can be produced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] An embodiment of the present invention will be described below, but the contents of the present invention are not limited to the description of the embodiment below.

[0017] <Lithium-ion secondary battery> The lithium ion secondary battery according to this embodiment includes a positive electrode and a negative electrode as electrodes, a separator that electrically insulates the positive electrode and the negative electrode, an electrolyte, and an exterior body that contains them. Inside the exterior body, the positive electrode and the negative electrode face each other with the separator in between, and at least a portion of the separator is immersed in the electrolyte.

[0018] [Electrodes for lithium-ion secondary batteries] The positive electrode includes a positive electrode mixture layer as an electrode mixture layer formed on a positive electrode current collector, and the negative electrode includes a negative electrode mixture layer as an electrode mixture layer formed on a negative electrode current collector. The lithium ion secondary battery electrode according to the present embodiment may be applied to either a positive electrode or a negative electrode. In particular, it is preferable to apply the electrode to a negative electrode, which tends to have a large volume change due to insertion and desorption of lithium ions during charging and discharging.

[0019] (electrode mixture layer) The positive electrode mixture layer includes at least a positive electrode active material, a dendritic polymer, and a binder as electrode active materials. Similarly, the negative electrode mixture layer includes at least a negative electrode active material, a dendritic polymer, and a binder as electrode active materials. In addition to the above, the electrode mixture layer may include a conductive assistant. Countless particles of the electrode active material are arranged in the electrode mixture layer in an aggregated state. The dendritic polymer is chemically bonded to the particle surfaces of the electrode active material. In addition, the dendritic polymer is chemically bonded to the binder. This makes it possible to increase the binding force between the electrode active materials without increasing the amount of binder, to maintain the density of the electrode active material, and to reduce the expansion and contraction of the electrode during charging and discharging.

[0020] The density of the electrode mixture layer after impregnation with the electrolyte is preferably 95% or more of the density of the electrode mixture layer before impregnation with the electrolyte. This makes it possible to prevent a decrease in density of the electrode active material of the electrode due to impregnation with the electrolyte. In addition, it is possible to minimize the space inside the battery cell that is required in the design of a lithium ion secondary battery, taking into account the variation in the thickness and width of the electrode. Therefore, it is possible to improve the volumetric energy density of the lithium ion secondary battery. From the above viewpoint, the density of the negative electrode mixture layer after impregnation with the electrolyte is 1.4 g / cm. 3 More preferably, it is equal to or greater than this.

[0021] (electrode active material) Examples of the negative electrode active material include carbon powder (amorphous carbon), silica (SiO x), titanium composite oxides (Li4Ti5O7, TiO2, Nb2TiO7), tin composite oxides, lithium alloys, metallic lithium, etc., can be used alone or in combination. As the carbon powder, one or more of soft carbon (easily graphitized carbon), hard carbon (hardly graphitized carbon), and graphite can be used.

[0022] The positive electrode active material is, for example, a lithium composite oxide (LiNi x Co y Mn z O2(x+y+z=1), LiNi x Co y Al z O2 (x+y+z=1), lithium iron phosphate (LiFePO4 (LFP)), etc. can be used. The above may be used alone or in combination of two or more.

[0023] At least a portion of the electrode active material preferably has a hydroxyl group or a carboxyl group, which allows the dendritic polymer to be chemically bonded to the surface of the electrode active material.

[0024] (Dendritic Polymers) Dendritic polymers are a general term for polymers having a branched structure, such as dendrons, dendrimers, and hyperbranched polymers.

[0025] The dendrons can be synthesized by a conventional method, or commercially available products can be used, such as those available from Aldrich. Specific examples of dendrons available from Aldrich include, for example, polyester-8-hydroxyl-1-acetylene bis-MPA dendron, 3rd generation (catalog number: 686646), polyester-16-hydroxyl-1-acetylene bis-MPA dendron, 4th generation (catalog number: 686638), polyester-32-hydroxyl-1-acetylene bis-MPA dendron, 5th generation (catalog number: 686611), polyester-8-hydroxyl-1-carboxyl bis-MPA dendron, 3rd generation (catalog number: 686670), polyester-16-hydroxyl-1-carboxyl bis-MPA dendron, 4th generation (catalog number: 686662), polyester-32-hydroxyl-1-carboxyl bis-MPA dendron and 5th generation (catalog number: 686654).

[0026] The dendrimers can be synthesized by conventional methods, or are commercially available from Aldrich. For example, polyamidoamine dendrimer, ethylenediamine core, generation 0.0 (catalog number: 412368), polyamidoamine dendrimer, ethylenediamine core, generation 1.0 (catalog number: 412368), polyamidoamine dendrimer, ethylenediamine core, generation 2.0 (catalog number: 412406), polyamidoamine dendrimer, ethylenediamine core, generation 3.0 (catalog number: 412422), polyamidoamine dendrimer, ethylenediamine core, generation 4.0 (catalog number: 412446), polyamidoamine dendrimer, ethylenediamine core, generation 5.0 (catalog number: 536709), polyamidoamine dendrimer, ethylenediamine core, generation 6.0 (catalog number: 536717), polyamidoamine dendrimer, ethylenediamine core, generation 7.0 (catalog number: 536725), and the like, each of which has an amino group at the end. In addition to the terminal amino group, hydroxyl, carboxyl and trialkoxysilyl groups are also available.

[0027] Hyperbranched polymers can be synthesized using standard methods or are available commercially from Aldrich, such as Hyperbranched Bis-MPA Polyester-16-hydroxyl, 2nd generation (catalog number: 686603), Hyperbranched Bis-MPA Polyester-32-hydroxyl, 3rd generation (catalog number: 686581), and Hyperbranched Bis-MPA Polyester-64-hydroxyl, 4th generation (catalog number: 686573).

[0028] The amount of the dendritic polymer chemically bonded to the surface of the electrode active material is preferably 0.1 to 1.0 part by mass relative to 100 parts by mass of the electrode active material. More preferably, it is 0.25 to 1.0 part by mass. This makes it possible to suppress swelling of the electrode without increasing the amount of the binder component in the electrode. Therefore, it is possible to improve the energy density of the electrode and the lithium ion secondary battery cell.

[0029] It is preferable that the dendritic polymer has a branched structure within a certain range and has a functional group at the end capable of a cross-linking reaction. This maintains the bonding strength between the active materials, while the branched structure with a moderate molecular weight does not inhibit the movement of lithium ions, so that a low-resistance cell can be created even if a high-density electrode body is formed in the cell. Preferred examples of dendritic polymers are shown below. The dendritic polymers shown below are characterized by being electrochemically stable and not easily decomposed in the battery.

[0030] The dendritic polymer preferably has four or more molecular terminals in one molecule. It is also preferable that the dendritic polymer has a specific functional group, which will be described later. When the dendritic polymer has a number of molecular terminals within the above range, the probability of the specific functional group coming into contact with the electrode active material increases when the molecular terminal has a specific functional group. Therefore, the amount of the dendritic polymer chemically bonded to the electrode active material is within an appropriate range, and the dendritic polymer can be strongly chemically bonded to cover the surface of the electrode active material. It is more preferable that the dendritic polymer has four or more and 64 or less molecular terminals. It is even more preferable that the specific functional group has eight or more hydroxyl groups and at least one carboxyl group. Thereby, for example, the dendritic polymer and the electrode active material are dehydrated and condensed to form an ether bond. The specific functional group can also be imparted to the terminal active group of the dendritic polymer exemplified above by any reaction.

[0031] The number-average molecular weight of the dendritic polymer is preferably 300 or more and 100,000 or less, more preferably 800 or more and 10,000 or less. If the number-average molecular weight is within the above range, the lithium ion intercalation surface on the surface of the electrode active material particles can be sufficiently covered, and direct contact of the lithium ion intercalation surface with the electrolyte can be suppressed, thereby improving the durability of the electrode and the electrolyte. In addition, the electrode mixture layer is covered with the dendritic polymer to an extent that does not hinder the movement of lithium ions, and therefore good lithium ion conductivity of the electrode mixture layer can be obtained.

[0032] (Binder) The binder forms a chemical bond with the dendritic polymer. For example, the binder forms an ether bond by a dehydration condensation reaction with the dendritic polymer. The binder preferably has at least one of a hydroxyl group, a carboxyl group, a sulfonic acid group, a sulfinic acid group, a phosphoric acid group, and a phosphonic acid group.

[0033] Examples of binders include cellulose-based polymers, fluorine-based resins, vinyl acetate copolymers, rubbers, etc. Specifically, examples of binders when a solvent-based dispersion medium is used include polyvinylidene fluoride (PVDF), polyimide (PI), polyvinylidene chloride (PVDC), polyethylene oxide (PEO), etc., and examples of binders when a water-based dispersion medium is used include styrene butadiene rubber (SBR), acrylic acid-modified SBR resin (SBR-based latex), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), hydroxypropyl methylcellulose (HPMC), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), etc. The above may be used alone or in combination of two or more.

[0034] (Conductive assistant) Examples of the conductive assistant include carbon black such as acetylene black (AB) and ketjen black (KB), carbon materials such as graphite powder, conductive metal powders such as nickel powder, etc. The above may be used alone or in combination of two or more.

[0035] (current collector) The materials for the positive electrode current collector and the negative electrode current collector may be copper, aluminum, nickel, titanium, stainless steel foil or plate, carbon sheet, carbon nanotube sheet, etc. The above materials may be used alone, or metal clad foil made of two or more materials may be used as necessary. The thickness of the positive electrode current collector and the negative electrode current collector is not particularly limited, but may be, for example, in the range of 5 to 100 μm. From the viewpoint of improving the structure and performance, the thickness of the positive electrode current collector 2 and the negative electrode current collector 5 is preferably in the range of 7 to 20 μm.

[0036] [Separator] The separator is not particularly limited, but examples thereof include porous resin sheets (films, nonwoven fabrics, etc.) made of resins such as polyethylene (PE), polypropylene (PP), polyester, cellulose, and polyamide.

[0037] [Electrolyte] The electrolyte may be made of a non-aqueous solvent and an electrolyte. The concentration of the electrolyte is preferably in the range of 0.1 to 10 mol / L. The electrolyte may contain an additive containing at least one compound selected from the group consisting of vinylene carbonate, fluoroethylene carbonate, and propane sultone. By using an electrolyte containing a compound that has reductive decomposition properties and is likely to form an SEI film, the added compound is decomposed preferentially to the electrolyte to form an SEI film on the negative electrode, thereby improving the durability of the electrolyte.

[0038] (Non-aqueous solvent) The non-aqueous solvent is not particularly limited, and examples thereof include aprotic solvents such as carbonates, esters, ethers, nitriles, sulfones, lactones, etc. Specific examples thereof include ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), tetrahydrofuran (THF), 2-methyltetrahydrofuran, dioxane, 1,3-dioxolane, diethylene glycol dimethyl ether, ethylene glycol dimethyl ether, acetonitrile (AN), propionitrile, nitromethane, N,N-dimethylformamide (DMF), dimethyl sulfoxide, sulfolane, γ-butyrolactone, etc.

[0039] (electrolyte) Examples of the electrolyte contained in the electrolytic solution include LiPF6, LiBF4, LiClO4, LiN(SO2CF3), LiN(SO2C2F5)2, LiCF3SO3, LiC4F9SO3, LiC(SO2CF3)3, LiF, LiCl, LiI, Li2S, Li3N, Li3P, Li 10 GeP2S 12 (LGPS), Li3PS4, Li6PS5Cl, Li7P2S8I, Li x PO y Nz (x=2y+3z-5, LiPON), Li7La3Zr2O 12 (LLZO), Li 3x La 2 / 3-x TiO3(LLTO), Li 1+x Al x Ti 2-x (PO4)3(0≦x≦1, LATP), Li 1.5 Al 0.5 Ge 1.5 (PO4)3(LAGP), Li 1+x+y Al x Ti 2-x SiyP 3-y O 12 , Li 1+x+y Al x (Ti,Ge) 2-x SiyP 3-y O 12 , Li 4-2x Zinc x GeO4 (LISICON), etc. Among them, it is preferable to use LiPF6, LiBF4, or a mixture thereof as the electrolyte.

[0040] In addition to the above, examples of the electrolyte include ionic liquids or ionic liquids containing polymers containing aliphatic chains such as polyethylene oxide (PEO) and polyvinylidene fluoride (PVDF) copolymers. An electrolyte containing an ionic liquid can flexibly cover the surface of an electrode active material and can form a site for ion migration in contact with the surface of the electrode active material.

[0041] <Method of manufacturing electrodes for lithium-ion secondary batteries> The manufacturing method of the lithium ion secondary battery according to this embodiment includes an electrode mixture layer forming step of forming an electrode mixture layer containing an electrode active material, a dendritic polymer, and a binder on a current collector, a pressing step of forming an electrode by pressing the current collector on which the electrode mixture layer has been formed at a first temperature, and a vacuum drying step of vacuum drying the electrode formed by the pressing step at a second temperature.

[0042] (Electrode composite layer formation process) The electrode mixture layer forming step may include, for example, a stirring step of stirring a mixture of an electrode active material and a dendritic polymer, a reduced pressure drying step of drying the mixture under reduced pressure after the stirring step, an electrode paste preparation step of mixing the mixture with a binder and dispersing the mixture in a solvent after the reduced pressure drying step to prepare an electrode paste, and an electrode paste application step of applying the electrode paste onto a current collector and drying it. The electrode mixture layer forming step is not limited to the above as long as it is possible to form an electrode mixture layer on a current collector.

[0043] The reduced pressure drying step is a step of drying a mixture of an electrode active material and a dendritic polymer under reduced pressure for a predetermined temperature and time, for example, to chemically bond the dendritic polymer to the surface of the electrode active material. The temperature during reduced pressure drying can be 100 to 200° C., and is preferably 120 to 150° C. The drying time is preferably 12 hours or longer.

[0044] (Pressing process) The pressing step is a step of forming an electrode by pressing the current collector on which the electrode mixture layer is formed at a first temperature. The first temperature can be, for example, room temperature to 200° C., and is preferably 120° C. to 160° C. The method of pressing is not particularly limited, but for example, roll pressing, hot pressing, etc. can be used.

[0045] (Vacuum drying process) The vacuum drying step is a step of vacuum drying the electrode that has been subjected to the pressing step at a second temperature. This step forms chemical bonds between the electrode active materials chemically bonded to the dendritic polymer, and between the dendritic polymer and the binder. The second temperature can be, for example, 120 to 200°C. The second temperature is preferably 120°C to 160°C. If the second temperature exceeds 200°C, it may exceed the heat resistance temperature of the binder, and the effect of suppressing the swelling of the electrode decreases. If the second temperature is less than 120°C, it takes time for the water generated by the dehydration reaction to be discharged from the electrode mixture layer having a pore structure, and the production efficiency decreases. The vacuum condition in the vacuum drying step can be, for example, -98 kPa or less.

[0046] By adjusting the first temperature in the pressing process and the second temperature in the vacuum drying process, the density of the electrode mixture layer after impregnation with the electrolyte can be adjusted to 95% or more of the density of the electrode mixture layer before impregnation with the electrolyte. The first temperature can be adjusted, for example, by a non-contact thermometer attached to the roll press. The second temperature can be adjusted by a thermometer such as a thermistor attached to the vacuum high-temperature tank. EXAMPLES

[0047] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the description of the following examples.

[0048] The negative electrode plate according to Example 1 was produced by the following procedure. First, 0.1 parts by mass of dendron (polyester-32-hydroxyl-1-carboxyl bis-MPA dendron, 5th generation) as a dendritic polymer was weighed out relative to 100 parts by weight of graphite as an electrode active material, and stirred in an aqueous solution for 1 hour. Then, the mixture was dried under reduced pressure for 16 hours at 150°C to obtain a negative electrode material in which a dendritic polymer was bonded to the surface of the electrode active material. It is considered that all of the dendrons as the dendritic polymer are chemically bonded to the surface of the electrode active material. Next, carboxymethyl cellulose (CMC) and a conductive assistant were mixed and dispersed using a planetary mixer. Then, the negative electrode material obtained above was mixed and dispersed again using a planetary mixer. Then, a dispersion solvent and styrene butadiene rubber (SBR) were added and dispersed to produce an electrode paste. This electrode paste was applied to a Cu current collector and dried.

[0049] The Cu current collector on which the electrode paste was applied and dried was pressed with a roll press at room temperature. This was placed in a vacuum drying furnace, heated to a vacuum drying temperature of 120° C., and a condensation reaction was carried out at −98 kPa or less for 12 hours to produce the negative electrode plate of Example 1. For the electrodes of the other examples and comparative examples, the negative electrode plates of each example and comparative example were also produced in the same manner as in Example 1, except that the dendritic polymer content, pressing temperature, and vacuum drying temperature were as shown in Table 1.

[0050] [Mixture density retention rate] The negative electrode plates according to each of the examples and comparative examples were punched out to a diameter of 16 mm to prepare test pieces. The thickness of the film at room temperature after vacuum drying was measured with a micrometer, and the weight was measured to determine the density (g / cm 3 ) was calculated. Then, 10 μL of a mixed solvent of ethylene carbonate (EC):diethyl carbonate (DEC):EMC = 3:4:4 (volume ratio) was dropped onto the test piece, and a glass plate was placed on top to prevent the solvent from drying. After 30 minutes had passed, the glass plate was removed and excess solvent was removed by soaking Kimwipe. After visually confirming that the solvent had been removed, the film thickness of the test piece was measured with a micrometer, the weight was measured, and the density (g / cm) of the test piece after the solvent had been dropped was calculated. 3 The ratio of the density of the test piece after the solvent was dropped to the density of the test piece before the solvent was dropped was defined as the composite density retention rate (%). The results are shown in Table 1.

[0051] [Preparation of lithium-ion secondary batteries] The negative electrode plates according to the respective Examples and Comparative Examples were used to fabricate lithium ion secondary batteries.

[0052] (Preparation of positive electrode) Conductive additive and polyvinylidene fluoride (PVDF) are mixed and dispersed in a rotation and revolution mixer, and then Li1Ni is used as the positive electrode active material. 0.6 Co 0.2 Mn 0.2 O2 (NCM622) was mixed and mixed using a planetary mixer. N-methyl-N-pyrrolidinone (NMP) was then added to prepare an electrode paste. This electrode paste was applied to an Al current collector, dried, pressed with a roll press, and dried in a vacuum at 120°C to prepare a positive electrode plate. The electrode plate prepared was punched to 30 mm x 40 mm. The thickness of the positive electrode plate was 70 μm.

[0053] A laminate with a separator sandwiched between the negative and positive electrodes prepared above was introduced into a container made by heat-sealing aluminum laminate for secondary batteries (manufactured by Dai Nippon Printing Co., Ltd.) into a bag-shaped container, and an electrolyte was injected into the interface between the electrodes to prepare a lithium-ion secondary battery. The electrolyte used was a solution in which LiPF6 was dissolved to a concentration of 1.2 mol / L in a solvent made by mixing ethylene carbonate, ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 30:30:40. The following tests were performed using the prepared lithium-ion secondary battery.

[0054] [10s asst initial resistance measurement] The 10s asst initial resistance measurement of the lithium ion secondary battery according to each example and comparative example was carried out by the following method. First, the charge level (SOC (State of Charge)) of the lithium ion secondary battery was adjusted to 50%. Next, the C rate was set to 0.5C and pulse discharged for 10 seconds, and the voltage at 10 seconds discharge was measured. Then, the voltage at 10 seconds discharge was plotted against the current at 0.2C, with the horizontal axis being the current value and the vertical axis being the voltage. Next, after leaving it for 5 minutes, supplementary charging was performed to return the SOC to 50%, and then it was left for another 5 minutes. Next, the above operation was carried out for each C rate of 1C, 1.5C, 2C, 2.5C, and 3C, and the voltage at 10 seconds discharge against the current at each C rate was plotted. Then, the slope of the approximation line obtained from each plot was taken as the 10s asst initial cell resistance of the lithium ion secondary battery. The results are shown in Table 1.

[0055] [Table 1]

[0056] From the results in Table 1, it was confirmed that the electrodes for lithium ion secondary batteries according to each Example have a higher composite density retention rate than the electrodes for lithium ion secondary batteries according to the comparative examples, and are capable of preventing a decrease in density of the electrode active material of the electrode.

Claims

1. An electrode for a lithium ion secondary battery, The electrode comprises an electrode active material, a dendritic polymer, and a binder, The dendritic polymer is chemically bonded to a surface of the electrode active material, the dendritic polymer and the binder are chemically bonded to each other, The dendritic polymer has eight or more hydroxyl groups and at least one carboxyl group at the molecular terminals. Electrode for lithium-ion secondary batteries.

2. The electrode active material is a negative electrode active material, 2. The electrode for a lithium ion secondary battery according to claim 1, wherein a density of a negative electrode mixture layer including the electrode active material, the dendritic polymer, and the binder after being impregnated with an electrolyte solution is 95% or more of a density of the negative electrode mixture layer before being impregnated with the electrolyte solution.

3. The electrode active material is a negative electrode active material, 3. The electrode for a lithium ion secondary battery according to claim 1, wherein an amount of the dendritic polymer chemically bonded to a surface of the negative electrode active material is 0.1 to 1.0 parts by mass per 100 parts by mass of the negative electrode active material.

4. A method for producing an electrode for a lithium ion secondary battery, comprising the steps of: an electrode mixture layer forming step of forming an electrode mixture layer containing an electrode active material, a dendritic polymer, and a binder on a current collector; a pressing step of pressing the current collector on which the electrode mixture layer is formed at a first temperature to form an electrode; a vacuum drying step of vacuum drying the electrode formed by the pressing step at a second temperature, the electrode mixture layer forming step includes a reduced pressure drying step of drying the mixture of the electrode active material and the dendritic polymer under reduced pressure at a temperature of 100 to 200° C., thereby chemically bonding the dendritic polymer to a surface of the electrode active material; The dendritic polymer has eight or more hydroxyl groups and at least one carboxyl group at the molecular terminals.

5. 5. The method for producing an electrode for a lithium ion secondary battery according to claim 4, wherein the density of the electrode mixture layer after impregnation with the electrolyte is adjusted to 95% or more of the density of the electrode mixture layer before impregnation with the electrolyte by adjusting the first temperature and the second temperature.

Citation Information

Patent Citations

  • Lithium secondary battery and its manufacture

    JP2000285966A

  • JPP6527626B

  • Electrode for secondary battery and lithium ion secondary battery using same

    WO2016185925A1